Efforts to Improve Science Learning Outcomes Through the STAD Type Cooperative Model - Ninin Indira; Vivi Ari Adianti; Siti Masitho Desinta Rizkya (Journal of Action Research in Education, 2023)
This study aims to determine the learning outcomes of science, specifically regarding changes in the state of matter, and the learning activities of fourth-grade students at Tanjung Jati 2 State Elementary School through the implementation of the STAD cooperative learning model. The study concludes that the percentage of mastery obtained through individual and classical completeness with the application of the STAD cooperative learning model, before intervention, was 42%. In the first cycle, it increased to 65%, and in the second cycle, the improvement reached 80%. It can be concluded that the use of the STAD cooperative learning model (Student Teams Achievement Division) effectively enhances motivation and science learning outcomes, particularly in the topic of changes in the state of matter, reaching up to 80%.